2007
DOI: 10.1097/01.prs.0000259190.56177.ca
|View full text |Cite
|
Sign up to set email alerts
|

Nonsynostotic Occipital Plagiocephaly: Factors Impacting Onset, Treatment, and Outcomes

Abstract: This study demonstrates trends that may predict additional risks for developing nonsynostotic occipital plagiocephaly, including torticollis, plural births, and increased socioeconomic affluence. In addition, the nonsynostotic occipital plagiocephaly cohort was breast-fed less than the general population, demonstrating that breast-feeding may be preventative, as breast-fed infants are repositioned more frequently and sleep for shorter periods. As in other studies, cranial molding helmet therapy was more effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 21 publications
3
71
2
1
Order By: Relevance
“…Most often, the vertex of the head lies within the birth canal with a left occipital anterior presentation. 20 In this position, the infant' s right occiput is compressed against the maternal pelvis and the left forehead against the lumbosacral spine. 20,28 This position may initiate a process that may be perpetuated by postnatal supine sleep positioning, resulting in the preference to rightsided head turning and allowing for a position of comfort to be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often, the vertex of the head lies within the birth canal with a left occipital anterior presentation. 20 In this position, the infant' s right occiput is compressed against the maternal pelvis and the left forehead against the lumbosacral spine. 20,28 This position may initiate a process that may be perpetuated by postnatal supine sleep positioning, resulting in the preference to rightsided head turning and allowing for a position of comfort to be established.…”
Section: Discussionmentioning
confidence: 99%
“…The helmet approach to treating positional plagiocephaly has been proven effective and is well documented. [12][13][14][15][16][17][18][19][20][21][22][23][24] However, little research has been undertaken to determine the incidence of positional plagiocephaly. Clinicians working at Head Shape Clinics in Canada have reported anecdotally more infants attending these specialty clinics.…”
mentioning
confidence: 99%
“…Six articles were excluded because they were not directly related to cranial orthoses therapy in deformational plagiocephaly (n = 5), or involved nonhuman subjects (n = 1). Of the remaining 36 papers, 21 were primary research literature articles, 5,6,[9][10][11][12][13][14][15][16][17]20,25,26,31,33,[35][36][37]39,41 12 were reviews, 7,8,[22][23][24]29,30,32,34,38,40,42 2 were letters, 3,18 and 1 described the methodology of an ongoing randomized controlled trial. 43 Of the 21 primary research articles, there were 7 Class II studies, 10,11,13,17,25,31,36 1 Class III study, 33 and 13 Class IV studies.…”
Section: Resultsmentioning
confidence: 99%
“…These cranial orthotic devices cost anywhere from $1000 to $3500. 23 Part of the high cost is secondary to the fact that the companies that make most devices pride themselves on custom-making the orthosis for the baby. However, Thompson et al reported positive results in 2009 while using a generic-sized soft foam helmet that was fitted to patients by applying extra foam padding.…”
Section: Helmet Therapy In Comparison With Conservative Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation